2022
DOI: 10.23889/ijpds.v7i1.1694
|View full text |Cite
|
Sign up to set email alerts
|

Data Resource: Children Receiving Care and Support and Children in Need, administrative records in Wales.

Abstract: IntroductionIn Wales, the Children in Need (CIN) dataset includes information relating to needs of children and social care support. Before the Social Services and Well-being (Wales) Act 2014 came into force in April 2016, this data collection was named the Children in Need census, changing to Children Receiving Care and Support (CRCS) after this date to reflect better the children eligible for inclusion. This paper describes these datasets, their potential for research and their limitations. We describe data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The UPN is only recorded for school-aged children, predominantly those over four years old, though some children (e.g. those eligible for the Flying Start programme) may have a UPN when they are as young as two years old [ 16 , 17 ]. The change in the legal framework from the 1989 Act to the 2014 Act has led to the modification of the information collected in some fields, with ethnicity recorded post-2014 Act being placed in much broader categories than earlier collections.…”
Section: Children Looked After Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UPN is only recorded for school-aged children, predominantly those over four years old, though some children (e.g. those eligible for the Flying Start programme) may have a UPN when they are as young as two years old [ 16 , 17 ]. The change in the legal framework from the 1989 Act to the 2014 Act has led to the modification of the information collected in some fields, with ethnicity recorded post-2014 Act being placed in much broader categories than earlier collections.…”
Section: Children Looked After Datasetsmentioning
confidence: 99%
“…Similarly to the Welsh Children In Need (CIN) and Children in Receipt of Care and Support (CRCS) censuses [ 17 ], the Children Looked After collection also records the main reason a child receives care and support services. Children captured in the Children Looked After census will generally be included in the CIN or CRCS censuses, provided they meet the date criteria for inclusion in these <cite our paper>, and therefore will also have their need for care and support recorded there.…”
Section: Children Looked After Datasetsmentioning
confidence: 99%
“…Validation of immunisation flags showed around 70% of immunisation flags were potentially correct. Some previous studies have examined immunisation rates of looked after children in comparison with the general population, but few have included other groups of children receiving statutory social work services (21). Of the few studies that have focused on immunisations in children 'looked-after, ' previous work has consistently demonstrated that this population are less likely to be up-to-date with their immunisations compared to children not in care (4,9,32,33), with the exception of one study which reported that children 'looked-after' are more likely to be fully immunised against MMR (84%) compared to not 'looked-after' children (80.8%) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Information on date of birth and sex assigned at birth was obtained from the Welsh Demographic Service Dataset (WDSD), which is a demographics register of people registered with a general practice (GP) in Wales. Children Wales (LACW), and Children in Need Wales (CINW) census data (Lee et al, 2022).…”
Section: Methods Datamentioning
confidence: 99%
“…Information on ethnicity came from the Office for National Statistics (ONS) Census 2011: Welsh Records (CENW), covering 68.9% of the study population. Information on young people who have had contact with social services came from linked databases held by Welsh Government, including the Children Receiving Care and Support (CRCS), Looked After Children Wales (LACW), and Children in Need Wales (CINW) census data (Lee et al, 2022).…”
Section: Methodsmentioning
confidence: 99%